Giant Chondrosarcoma of the Clavicle - A Case Report and Literature Review. (Journal of Pakistan Orthopaedic Association, 2020)
The most common tumours of the clavicle are Myeloma and Ewing’s sarcomas while chondrosarcomas being a relative rarity at this location. However, a clavicular chondrosarcoma is considered favourable compared to the traditional more challenging locations like pelvis, femur and humerus. The subcutaneous location of the clavicle facilitates early detection. A further favourable consideration is that a complete claviculectomy without incurring significant morbidity can be performed. We reported an adult male patient who presented to our unit with a massive clavicular chondrosarcoma with radiological spread to the retro-pectoral lymph nodes. A total claviculectomy was performed with en bloc removal in the first stage followed by local lymph node clearance and adjuvant chemotherapy and radiotherapy. At one year follow up no recurrence was noted and the patient had good functions of the shoulder. We recommend total claviculectomy as the procedure of choice for clavicular chondrosarcomas.